Sustainable Building and Indoor Air Quality - González Lezcano, Roberto Alonso (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue addresses a topic of great contemporary relevance; in developed countries, most of peoples' time is spent indoors and, depending on each person, the presence in the home ranges from 60% to 90% of the day, and 30% of that time is spent sleeping. Taking into account these data, indoor residential environments have a direct influence on human health. In addition to this, in developing countries, significant levels of indoor pollution make housing unsafe, with a detrimental impact on the health of inhabitants. Housing is therefore a key health factor for people all over the world, and various parameters such as air quality, ventilation, hygrothermal comfort, lighting, physical environment, and building efficiency, among others, can contribute to healthy architecture, and the conditions that can result from the poor application of these parameters.